Returning sanity to the classroom : eliminating the testing mania - Lucido, Horace, 1945- (Rowman and Littlefield, 2015)
Over the millennia humans have employed a natural method of 'learning from their mistakes' to achieve success. They address these faulted situations repeatedly, making appropriate changes along the way. This practice is the heart and soul of our creativity and inventiveness. Returning Sanity to the Classroom presents a classroom method of codifying this natural process of student learning centered on their freedom to readdress academic mistakes without penalty.